Al-Wasatiyyah Min Manzur Al-Quran Al-Karim - Muhamad Zaid, Ismail (2016)
The word ‘al-wasatiyyah’ ( الوسطية ) in the Qur’an, which literally means moderation, is considered among the words that are repeated in several places in the Qur’an and used in various linguistic contexts, either explicitly or implicitly. However, these contexts are not evident unless they are scrutinized attentively. Therefore, this research aims to identify several linguistic issues that bear the concept of ‘wasatiyyah’ (moderation) in the Qur’an by scrutinizing its linguistic textual contexts. This study uses descriptive and analytical approaches, relying on studies that have focused on the linguistic meaning of ‘wasatiyyah’. This study found that the word ‘ وسط ’ (moderate) was stated explicitly in the Qur’an in five places with different formations. The Qur’an also pointed to the concept of ‘wasatiyyah’ in different terms in accordance with the Qur’anic linguistic methodology. This study also suggests that understanding the Arabic language has a significant impact in reflecting on the right meanings of the word ‘wasatiyyah’ and in identifying its legitimate meaning because the knowledge of Arabic vocabulary and the comprehension of Arabic terms are necessary to understand different contexts of the Qur’anic texts. Therefore, exercising close attention in identifying linguistic meanings is a must in selecting legitimate terms to link between the two concepts (linguistic and terminological).